Achieving Gender Equality and Empowering Women and Girls through Gender Responsive Budgeting in Ghana - Amoako Asiedu, Emelia (APPS Publications, 2023)
Gender inequality extracts enormous economic and human development costs, shifting fiscal policy to close the gaps and gains across societies. Gender responsive budgeting (GRB) is one of the approaches used by governments, international organizations, and civil society groups to promote and influence gender equality. The United Nations Development Fund for Women (UNIFEM) highlights in its 2020 report, that budgets in most countries are gender biased in their conceptualization, formulation, and implementation. In most African countries, and Ghana is no exception, unpaid care and gender differences in roles and responsibilities in household and the workplace are not considered in policy formulation and implementation. This research intends to answer the following questions; how have MDAs complied with GRB? What are the outcomes of implementing GRB in Ghana and what have been the key challenges to effective implementation? Using the qualitative approach with secondary data obtained from documents in some ministries in the Ghanaian public sector, this research attempted to answer the following questions; how have Ministries, Departments and Agencies (MDAs) complied with gender responsive budgeting (GRB)? What are the outcomes of implementing GRB in Ghana and what have been the key challenges to effective implementation? It was observed that Ghana’s constitution supported a strong enabling environment, with an explicit commitment to gender equality and women’s empowerment. The budget through which important national issues are anchored made specific allocations to address issues of women and girls for the years between 2008 to 2020, in the medium-term expenditure framework. This study contributes to academic literature, specifically on the issue of gender equality in the workplace. This study’s results and findings could be used as the reference for other studies and further research on gender equality and women’s rights.